P255 Utility of a screening protocol incorporating an interferon-gamma release assay (IGRA) on detection and decision to treat latent tuberculosis infection (LTBI) prior to anti-TNF therapy. (12th November 2015) - Zatyka, E; Nundoll, A; Breen, RAM; Price, N
Abstract : Introduction: Anti-TNFα treatment is associated with a significant risk of LTBI reactivation (median onset 12 weeks for infliximab). Patients are therefore recommended to undergo prior LTBI screening but current NICE and BTS guidance differ in their approach. In particular, the BTS places more emphasis on demographic factors (age, ethnicity, birth outside the UK) in stratifying risk and does not mandate routine IGRA use. 1 We describe the effect of local Trust screening protocol, incorporating IGRA, in the diagnosis and decision to start anti-TB chemoprophylaxis in a large cohort of patients being worked-up for anti-TNFα therapy. Methods: Data on adult patients undergoing LTBI screening before anti-TNFα commencement were collected prospectively between Jan '13 and Dec '14. The local screening protocol included clinical assessment, chest X-ray (CXR) and an ELISpot-TB assay. Where required, routine chemoprophylaxis was isoniazid for 6 months (anti-TNFα was started ≥1 month). Clinical follow-up data was obtained for 6 months post anti-TNFα commencement. Results: 472 patients received anti-TNFα for a minimum of 6 months after LTBI screening. According to the local protocol 21 cases (4.5%) received chemoprophylaxis vs. 66 patients (14%) who would have received chemoprophylaxis if the BTS guideline had been applied (Table 1 ). Moreover, 5 white, UK born, patients were identified that would not have been risk stratified to receive chemoprophylaxis according to the BTS. 2 cases receiving adalimumab for psoriasis developed active TB during the follow-up period. Both had negative IGRA at screening and were not given chemoprophylaxis however, both would have received treatment according to the BTS protocol. One case resulted from a subsequent TB exposure. The other had an abnormal screening CXR. This result was not appropriately followed up hence the case did not necessarily represent protocol failure per se . Conclusions: These preliminary data demonstrate the value of an LTBI screening IGRA based protocol by decreasing the need for chemoprophylaxis by 69% if BTS recommendations had been applied. Reference: 1 Ormerod, et al . BTS recommendations for assessing risk and for managing Mycobacterium tuberculosis infection and disease in patients due to start anti-TNF-α. Thorax 2005;60 :800–805